Frost Heave and Ice Lenses Formation in Freezing Soils - Leonid Bronfenbrener (Journal of Chemical Engineering Research Updates, 2014)
A generalized model for secondary frost heave in freezing fine-grained soils is presented and discussed. The cryostatic suction effect, which increases upward water permeation, ice-lens growth during freezing, and, as a consequence, the increase of soil heave, is considered to be the main mechanism of moisture transfer. We recognize the need to determine the distribution of the moisture within the frozen fringe by approximation of the experimental data for the equilibrium unfrozen water content. This distribution is the result of the complicated interaction between water, ice and the mineral skeleton during the freezing process. The generalization of the Clapeyron relation, which is used in the studies of other authors, estimates only the drop in initial freezing temperature and does not define the connection with the external temperature gradient ∆T, which is responsible for the frost heave process. This very important aspect is discussed in detail in the introduction to our paper. We take also into account the ratio Pe/Ste # 1 (where Pe<<1). This approach allows us to obtain a more general solution. The criterion of the ice lenses formation in fine-grained soils and the model for calculation of the lenses' thickness and spacing are derived. The dynamics of the lenses formation in histogram form is presented and discussed. The theoretical results obtained from the solution for fine-grained soils are compared in good agreement with experimental investigations. The model presented predicts the frost heave and ice lenses formation in freezing soils with reasonable accuracy, satisfactorily reflects observed phenomena, and thus can be suitable for engineering practice.